Competence training in information technology for teachers of the University of Medical Sciences of Havana - Malena de los Milagros Zelada Pérez; Norberto Valcárcel Izquierdo (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: The scientific technological challenges characterize the 21st century require knowledge of the use of Information and Communication Technologies in the management of knowledge and academic improvement of professors, who need to develop Information Competencies. Objective: Identify central ideas, institutions, authors and more representative working groups within the published literature on information competencies. Material and methods: A literature review of 55 articles was carried out, 21 on the identification of IC in the teachers. The research was framed in a theoretical context within the field of Biomedical Sciences, from 2002, until 2018. They were located and consulted validated bibliographic sources, through the Virtual Health Library. The documentary analysis allowed to investigate the problem, to develop a teaching process according to the current society. Results: The authors consulted agree on the characteristics of the scientific-technological challenges of the 21st century. They agree on the situation of technological challenges in Cuba and in the Health sector, on the Information Literacy Program, which began in 2006. The international proposals on Information Competencies are an update of the original version published in 2008. Reflections are analyzed of authors and groups at the International level. Conclusions: Authors were identified who agree on the scientific and technological challenges that characterize this 21st century and focus their work towards the era of computerization. Keywords: Competence, Information Literacy, Information and Communications Technology, informational competences, Biomedicine.